Effect of different levels of saturated solution of calcium chloride in the preparation of calcium salt of fatty acid and its effect on rumen protozoa, pH and ammonia nitrogen (Bangladesh Journal of Animal Science, 2013)
Calcium salt of fatty acid was prepared by adding 3 different levels of saturated solution of calcium chloride (CaCl2) to soybean oil. It was found that fat content was not significantly affected by calcium chloride. However, calcium chloride had significant effect on other parameters like dry matter, fat, ash and sodium. The highest calcium and fat was obtained when 3.5 parts CaCl2 were added (p